BST2/Tetherin Enhances Entry of Human Cytomegalovirus - Viswanathan, Kasinath (Public Library of Science, 2011)
Interferon-induced BST2/Tetherin prevents budding of vpu-deficient HIV-1 by tethering mature viral particles to the plasma membrane. BST2 also inhibits release of other enveloped viruses including Ebola virus and Kaposi's sarcoma associated herpesvirus (KSHV), indicating that BST2 is a broadly acting antiviral host protein. Unexpectedly however, recovery of human cytomegalovirus (HCMV) from supernatants of BST2-expressing human fibroblasts was increased rather than decreased. Furthermore, BST2 seemed to enhance viral entry into cells since more virion proteins were released into BST2-expressing cells and subsequent viral gene expression was elevated. A significant increase in viral entry was also observed upon induction of endogenous BST2 during differentiation of the pro-monocytic cell line THP-1. Moreover, treatment of primary human monocytes with siRNA to BST2 reduced HCMV infection, suggesting that BST2 facilitates entry of HCMV into cells expressing high levels of BST2 either constitutively or in response to exogenous stimuli. Since BST2 is present in HCMV particles we propose that HCMV entry is enhanced via a reverse-tethering mechanism with BST2 in the viral envelope interacting with BST2 in the target cell membrane. Our data suggest that HCMV not only counteracts the well-established function of BST2 as inhibitor of viral egress but also employs this anti-viral protein to gain entry into BST2-expressing hematopoietic cells, a process that might play a role in hematogenous dissemination of HCMV.